Interpretation Of Stories In “Sabot-Ul Ojizin” By So‘Fi Olloyor (As Some Of His Stories) - Qizi, Abdullayeva Rufina Usman (Jurnal Pendidikan Jarak Jauh, 2024)
So‘fi Olloyor's work “Sabot ul-Ojizin” is a religious-ethical work, a book containing a description of the virtues that are highly regarded in the Islamic religion and stories corresponding to them. In this article, the analysis of such stories as ‘‘Hikoyati Sa’d-u Said’’, ‘‘Xalilulloh o‘g‘li Ismoil alayhissalom bayoni’’, ‘‘Hikoyati Abdulloh ibn Muborak’’, ‘‘Hikoyati shayx Imom Basriy’’ opinions about the artistic value and compositional structure of the work are stated.